Magnitude of Unintended Pregnancy and Associated Factors Among Pregnant Women in Debre Markos Town, East Gojjam Zone, Northwest Ethiopia: A Cross-Sectional Study - Nigussie K; Degu G; Chanie H; Edemealem H (Dove Medical Press, 2021)
Kumneger Nigussie,1 Genet Degu,1 Habtamu Chanie1 ,† Hayimro Edemealem2 1Department of Midwifery, College of Health Science, Debre Markos University, Debre Markos, Ethiopia; 2Department of Statistics, College of Natural and Computational Science, Debre Markos University, Debre Markos, Ethiopia†Mr Habtamu Chanie passed away on April 27, 2020Correspondence: Kumneger NigussieDepartment of Midwifery, College of Health Science, Debre Markos University, P.O. Box 269, Debre Markos, EthiopiaTel +251939636117Email kumnegernigussie21@gmail.comBackground: Unintended pregnancy is an important public health concern in both developing and developed countries due to its serious consequences for women, infants, families and communities, including the risk of unsafe abortion, delayed prenatal care, poor maternal mental health, poor child health outcomes and unemployment.Objective: The aim of the study was to assess the prevalence and associated factors of unintended pregnancy among pregnant women in the town of Debre Markos in 2019.Methods: The magnitude and associated factors of unintended pregnancy were assessed using a community-based cross-sectional study design. A multi-stage sampling technique was used to select five Kebeles (basic administrative units), and households were selected from the selected Kebeles using simple random sampling. A total of 580 samples were collected through standardized pretested questionnaires. Bivariate and multivariate logistic regression were used to analyze the relationship between the UP and independent variables.Results: Of the pregnant women, 202 (34.8%) (95% CI: 30.9– 38.7) participants had an unintended current pregnancy; of those 144 (24.8%) were mistimed pregnancies. Women aged 24 years were three times more likely to have an unintended pregnancy than those aged 35 years. Divorced and widowed women were four times more likely than women who were currently married to experience an unintended pregnancy. Gravidity 1– 2 and 3– 4 were 94% and 86% less likely than gravidity > 5 to experience an unintended pregnancy, and women who made family planning decisions on their own were less likely to have an unintended pregnancy.Conclusion: According to this study, the prevalence of unintended pregnancy was 34.8% and unintended pregnancy was significantly correlated with women’s age, marital status, gravidity and who made decisions on family planning. There is an obvious need to devise communication strategies on fertility and contraceptive issues between couples through peer education, and to encourage correct use of long-acting modern methods of family planning.Keywords: mistimed pregnancy, unintended pregnancy, unwanted pregnancy, women